Disfunção autonômica cardíaca em crianças e adolescentes obesos após manobra de Valsalva - Rocha, Aracele Toscano (2018)
Childhood obesity is a major public health problem. The association between obesity and cardiac autonomic dysfunction among adults is already consensual, and in the pediatric age group it is still the reason for several investigations. Our study aimed to evaluate the cardiac autonomic modulation in obese children and adolescents, in the age group of 6 to 14 years of age, of both sexes, with no other associated comorbidities, by studying the heart rate variability. A descriptive statistical analysis of the data was performed. The ANOVA and the Pearson correlation test were used for the hypothesis tests, and the significance level adopted was set at p <0.05. A total of 59 children and adolescents were studied, of which 30 (49.2%) were male and 29 (50.8%) were female. Regarding the presence of puberty, 44 were prepubescent (74.6%) and 15 pubescent (25.4%). The children were grouped according to the body mass index (BMI), where 23 (39%) children were classified as eutrophic, 16 (27.1%) children classified as obese and 20 (33.9%) were classified as severe obese. All were submitted to anthropometric, clinical and laboratory evaluation, as well as the analysis of heart rate variability (HRV) using the Nerve Express® software, studying the variables in the time domain (SDNN) and in the frequency domain (TP, LF, HF, LF / HF), divided into 2 stages, the orthostatic test, followed by the Valsalva maneuver combined with deep breathing.. During the orthostatic test, there were no differences in the HRV indices between the eutrophic and obese / obese groups, both in the supine position and in the biped. In the analysis of HRV during the Valsalva maneuver combined with deep breathing, we found a reduction in parasympathetic activity, represented by the decrease of the HFun component in the obese group, mainly in the severe obese group (p = 0.010), and an increase in (p = 0.010) and the LF / HF ratio (p = 0.001) in the obese and severe obese group when compared to the eutrophic group. After these results, cardiac autonomic function impairment may be suggested in obese children and adolescents, especially in the severe obese. These findings are risk factors that, independently, may contribute to the increase of cardiovascular risk in this group.